PERANCANGAN APLIKASI PENCARIAN RUTE WISATA KULINER BERBASIS ANDROID MENGGUNAKAN ALGORITMA DIJKSTRA DI KOTA TANGERANG SELATAN - Maulana Syepanda; Zulhalim Zulhalim; Rachmawaty Haroen (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
South Tangerang is a city that has a culinary destination that is favored by many tourists. The difficulty of travelers in finding a place that is located in the alley or within a few tens of meters from the highway in South Tangerang need to be anticipated.. Application design the route of culinary tourism is an alternative that can minimize or even eliminate such difficulties. This research was conducted to develop an application created with the java programming language with the SDK and the application help of Google Maps API, and Location Based Service provides information on the geographical position of the place of food. The making of this app through several important stages, including requirements analysis, design, design implementation, and testing of the system are made.. Research and design of this application using the waterfall method and applying the algorithm of Dijkstra based on android. Use of this application is preceded by testing on the algorithm of Dijkstra and black box testing, so this app can be used properly. Based on the research that has been done, this application can be used to assist and facilitate tourists to find and to determine the shortest route to the location of the culinary tourism in the City of South Tangerang.